Fungsi Manajemen Diri Siswa SLTP dalam Memahami Pembelajaran Pendidikan Agama Islam (PAI) - Mindani, Mindani (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
In this paper the writer discusses the function of students’ self management in understanding Islamic learning and tries to relate it with general management function as a controlling system in learning. The indicators of students’ self management function will be seen in the following learning process such as the ability to set the goal of learning, monitor and evaluate the learning activity, and provide self reinforcement. Furthermore, it will also discuss about the implementation of student’s self management through some indicator; students, school and institution in applying learning management. Afterwards, it will also elaborate about to value, management and Islamic value and applying the student’s self management in learning process.Copyright © 2014 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v21i1.73